Pesticides survey and identification of common insecticides used for foodstuff storage in Makurdi, Benue State, Nigeria - Qrisstuberg M. Amua; Emmanuel K. Ukpoko (African Scientific Reports, 2025)
Pesticides in foodstuffs have become a daily deal with potential health challenges. Identification of these pesticides would be helpful in precautionary ways of dealing with their consequences on foodstuff and human health. A survey of pesticides was done in five major markets located in different axes of Makurdi town. The survey was achieved with the instrument of questionnaire and interview, anchored and recorded during the interview with pesticide sellers at their respective stores at the markets in Makurdi. At least three pesticide dealers were interviewed from each market on the types of pesticides available (inventory) comprehensively, those used for foodstuff storage, effective types of insecticide for foodstuff storage, the most patronized, and their mode of application. Identification and classification of the pesticides were based on active chemical names, common names, or trade names in Nigeria; the nature of active chemicals; applications on the field; and in-store foodstuff. The average percentage of daily patronage was calculated, and knowledge of the expiration date was uncertain. Interestingly, three active chemicals were considered the most popular and sought-after for aiding food storage: aluminum phosphide, dichlorvos, and permethrin, all under multiple brand names. These chemicals accounted for 37.50%, 33.33%, and 20.83% of the market, respectively, with the remaining insecticides accounting for just 8.33%. The study also revealed that many illegal and outdated pesticides are still in use in Makurdi, often in absurd quantities without a shelf life, endangering the health of everyone who consumes the food products obtained from their usage.